2009
DOI: 10.1073/pnas.0813360106
|View full text |Cite
|
Sign up to set email alerts
|

Type VI secretion apparatus and phage tail-associated protein complexes share a common evolutionary origin

Abstract: Protein secretion is a common property of pathogenic microbes. Gram-negative bacterial pathogens use at least 6 distinct extracellular protein secretion systems to export proteins through their multilayered cell envelope and in some cases into host cells. Among the most widespread is the newly recognized Type VI secretion system (T6SS) which is composed of 15-20 proteins whose biochemical functions are not well understood. Using crystallographic, biochemical, and bioinformatic analyses, we identified 3 T6SS co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
654
0
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 580 publications
(680 citation statements)
references
References 45 publications
15
654
0
11
Order By: Relevance
“…The T6SS spike complex is proposed to be formed by a VgrG trimer and a single PAAR protein (Leiman et al , 2009; Shneider et al , 2013). The central spike density has indeed well‐resolved features in the threefold symmetry reconstruction (Appendix Fig S1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The T6SS spike complex is proposed to be formed by a VgrG trimer and a single PAAR protein (Leiman et al , 2009; Shneider et al , 2013). The central spike density has indeed well‐resolved features in the threefold symmetry reconstruction (Appendix Fig S1A).…”
Section: Resultsmentioning
confidence: 99%
“…Evolutionarily related Type VI secretion system (T6SS) is used by bacteria to deliver proteins into both bacterial and eukaryotic cells (Mougous et al , 2006; Pukatzki et al , 2006; Hood et al , 2010; MacIntyre et al , 2010; Durand et al , 2014; Ho et al , 2014; Alcoforado Diniz et al , 2015; Hachani et al , 2016). The current model of T6SS biogenesis and mode of action is largely based on well‐understood phage assembly (Leiman et al , 2009; Lossi et al , 2011, 2013; Ho et al , 2014; Zoued et al , 2014; Clemens et al , 2015; Kudryashev et al , 2015; Cianfanelli et al , 2016). However, many important features are unknown mostly due to the lack of high‐resolution structural information of T6SS.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial T6SS clearly possesses proteins related to the contractile tail sheath, tube, BW1, BH2, and BS proteins (15), implying that this system is evolutionarily related to phage tails. Given that prophages provide the most abundant source of phage genes that could be adapted for other purposes by their bacterial hosts, it is probable the T6SS originally evolved from a prophage.…”
Section: Defining the Broadly Conserved Components Of The Simple Contmentioning
confidence: 99%
“…Functional and structural studies have shown that the T6SS nanomachine shares striking similarities with the bacteriophage tail structure (14)(15)(16)(17)(18)(19)(20)(21)(22). Accumulating evidence suggests that the baseplate complex is recruited into the membrane-associated protein complex and initiates the polymerization of a TssB-TssC (VipAVipB) contractile sheath.…”
mentioning
confidence: 99%